Mitochondrial DNA oxidation, methylation, and copy number alterations in major and bipolar depression - Ceylan, Deniz; Karacicek, Bilge; Tufekci, Kemal Ugur; Aksahin, Izel Cemre; Senol, Sevin Hun; Genc, Sermin (Frontiers in Psychiatry, 2023)
Background: Mood disorders are common disabling psychiatric disorders caused by both genetic and environmental f actors. Mitochondrial DNA (mtDNA) modif ications and epigenetics are promising areas of research in depression since mitochondrial dysf unction has been assoc iated with depression. In this study we aimed to investigate the mtDNA changes in depressive disorder (MDD) and bipolar disorder (BD). Methods: Displacement loop methylation (D-loop-met), relative mtDNA copy number (mtDNA-cn) and mtDNA oxidation (mtDNA-oxi) were investigated in DNA samples of individuals with MDD (n = 34), BD (n = 23), and healthy controls (HC; n = 40) using the Real-Time Polymerase Chain Reaction (RT-PCR). Blood samples were obtained f rom a subset of individuals with MDD (n = 15) during a depressive episode (baseline) and af ter remission (8th week).The study groups exhibited signif icant dif ferences in D-loop-met (p = 0.020), while relative mtDNA-cn and mtDNA-oxi showed comparable results. During the remission phase (8th week), there were lower levels of relative mtDNA-cn (Z = -2.783, p = 0.005) and D-loop-met (Z = -3.180, p = 0.001) compared to the acute MDD baseline, with no signif icant change in mtDNA -oxi levels (Z = -1.193, p = 0.233).Our f indings indicate signif icantly increased D -loop methylation in MDD compared to BD and HCs, suggesting distinct mtDNA modif ications in these conditions. Moreover, the observed alterations in relative mtDNA-cn and D-loop-met during remission suggest a potential role of mtDNA alterations in the pathophysiology of MDD. Future studies may provide valuable insights into the dynamics of mtDNA modif ications in both disorders and their response to treatment.